Tax Burden and Migration : A Political Economy Perspective - Sadka, Efraim; Razin, Assaf (Washington, D.C. : International Monetary Fund, 1997)
The extent of taxation and redistribution policy is generally determined at a political-economy equilibrium by a balance between those who gain and those who lose from a more extensive tax-transfer policy. In a stylized model of migration and human capital formation, we find, somewhat against conventional wisdom, that low-skill migration may lead to a lower tax burden and less redistribution than no migration, even though the migrants join the pro-tax coalition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet